Design and Implementation of a Website-Based E-Commerce Application Information System at PT. Fajar Lestari Sejati - Widiono, Rahayu (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this research is to create a website-based E-Commerce platform that can connect sellers with buyers. The method of this research uses qualitative methods through a descriptive approach. The qualitative research method is used by the author based on the goal of understanding the phenomenon occurring in the object under study. The descriptive approach is used by the author based on the goal of reflecting the existing situation or conditions in a structured and objective manner. The theory of this research uses the Software Development Life Cycle (SDLC) method with the Waterfall system life cycle model approach as the main approach in designing and implementing the website-based E-Commerce application information system. The result of this research is the creation of a website-based E-Commerce application information system which includes interactive website page displays, registration features, login features, sales menu features, product catalog features, payment transaction detail features, order status features, communication message features, product search features, product ordering features, shopping cart features, to payment transaction features that support various types of payment methods. The conclusion of this research is that the design and implementation carried out on the website-based E-Commerce application program produces an overview of the system process flow in the form of diagrams and produces several functional features that can be run and applied to online product sales and purchase activities or operational activities.